Studi Empiris: Produktivitas Kerja Karyawan - Abd. Mardan; Rahmisyari Rahmisyari; Arifin Arifin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to find out whether competence has a direct and significant effect on employee work productivity and whether competence has a direct and significant effect on employee work productivity through work motivation at PT. Bukit Tinoring Raya in Manado, the type of research used is quantitative with a survey method approach. The main data collection technique is through a questionnaire. The sampling method used was purposive sampling with a sample size of 150 respondents. The data analysis technique used in this research is the SEM Partial Least Square (PLS) method. The results of research hypothesis testing show that (i) competence does not directly have a significant effect on employee work productivity through work motivation, (ii). Competence has a significant effect on employee work productivity through work motivation.